2020
DOI: 10.1038/s41388-020-1285-5
|View full text |Cite
|
Sign up to set email alerts
|

Mortalin/HSPA9 targeting selectively induces KRAS tumor cell death by perturbing mitochondrial membrane permeability

Abstract: The mitochondrial HSP70 chaperone mortalin (HSPA9/GRP75) is often upregulated and mislocalized in MEK/ERK-deregulated tumors. Here, we show that mortalin depletion can selectively induce death of immortalized normal fibroblasts IMR90E1A when combined with K-Ras G12V expression, but not with wild type K-Ras expression, and that K-Ras G12V -driven MEK/ERK activity is necessary for this lethality. This cell death was attenuated by knockdown or inhibition of adenine nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…The mitochondrial HSP70 chaperone mortalin (HSPA9/GRP75) was often upregulated in MEK/ERK-deregulated tumors [48]. Wu et al [49] demonstrated that the depletion effect of HSPA9 was sensitized by KRAS activity, suggesting that HSPA9 was a potential target for KRAS-mutated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial HSP70 chaperone mortalin (HSPA9/GRP75) was often upregulated in MEK/ERK-deregulated tumors [48]. Wu et al [49] demonstrated that the depletion effect of HSPA9 was sensitized by KRAS activity, suggesting that HSPA9 was a potential target for KRAS-mutated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Many different aspects of mitochondrial biology directly influence tumorigenesis, including alterations to cell death pathways, mitochondrial dynamics, mitochondrial biogenesis and mTOR signalling, and oxidative stress [10]. A significant number of components of the mitochondrial import machineries are overexpressed in a variety of different cancers, including subunits of the TOM complex (Tom20, Tom40, Tom7 and Tom70) [186,[188][189][190][191][192], the TIM23 complex (Tim17a, Mortalin, Magmas, Tim50 and Tim23) [186,[193][194][195][196][197][198][199][200][201][202][203][204][205][206][207], the TIM22 complex (Tim22, AGK) [186,[208][209][210][211][212][213][214][215][216][217], the small Tim chaperones (Tim8a, Tim8b, Tim9, Tim13) [186,[218][219][220] and Mia40 [221,222]. In addition, two variants of Tim44 (C925A and G1274A) have been identified in oncocytic thyroid carcinomas [223].…”
Section: Mitochondrial Protein Import and Cancermentioning
confidence: 99%
“…TNMplot analysis reveals overexpression of several proteins involved in [4Fe-4S] trafficking from the mitochondria and to the cytosol and nucleus ( Table 2 ). The NEET family of proteins (CISD1/2) at the beginning of the CIA pathway is thought to be a novel cancer target [ 112 ]. CISD2 overexpression in murine xenograft breast cancer tumors resulted in increases in tumor size, aggressiveness, and the tolerance of cells to oxidative stress [ 113 ].…”
Section: Fe–s Biogenesis and Cancer Initiationmentioning
confidence: 99%